Optimalisasi Assistensi Pelaporan SPT Tahunan Orang Pribadi Dengan Program Tax Goes To Campus - Supriatiningsih; Hidayat Darwis (Politeknik Penerbangan Indonesia Curug, 2023)
Public awareness of tax obligations is still relatively low, and the pandemic has hampered Indonesia's economy, so assistance is needed to report annual taxes for individuals. The limitations that individual taxpayers often face in reporting their personal annual taxes and the purpose of paying taxes encourage us to take concrete action in the form of community service by assisting taxpayers in submitting SPT Online. The tax volunteer program was held due to limited partner resources in assisting taxpayers in increasing taxpayer compliance living around Setiabudi District in South Jakarta. The form of collaboration between the University of Technology Muhammadiyah Jakarta Tax Center and the Tax Division of the South Jakarta Regional Office 1 is realized as a tax volunteer providing tax reporting support services in March 2023. This activity is carried out with the aim of assisting taxpayers in compiling Individual Annual SPT.